1992
DOI: 10.1111/j.1365-313x.1992.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

The root-knot nematode resistance gene (Mi) in tomato: construction of a molecular linkage map and identification of dominant cDNA markers in resistant genotypes

Abstract: A dominant allele at the Mi locus on chromosome 6 of tomato (Lycopersicon esculentum Mill) confers resistance to three species of root-knot nematodes (Meloidogyne). The resistance, which is associated with a localized necrotic response, was originally introduced into tomato from the wild species Lycopersicon peruvianum. As a step towards the molecular cloning of Mi, we have identified closely linked DNA markers from both cDNA and genomic DNA libraries as restriction fragment length polymorphisms (RFLPs). DNA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 19 publications
2
61
0
Order By: Relevance
“…Pure virulent and avirulent lines of G. rostochiensis for the H 1 resistance gene in potato have been produced by Janssen et al [57] and with the help of these pure lines, they provided the only clear example of Mendelian proof for a gene-for-gene relation between a plant and a nematode [3,56]. Breeding attention has focussed on dominant resistance genes for economically important crops and a select number of them are currently the subject of RFLP-mapping programs as a prelude to the isolation of the actual resistance genes [4,32,46,63,65,76,86]. A potentially faster source of resistance genes may come from the Arabidopsis genome although an extensive screen with 74 ecotypes yielded no resistance against H. schachtii [ 102].…”
Section: Resistance Reactions Against Nematodesmentioning
confidence: 99%
“…Pure virulent and avirulent lines of G. rostochiensis for the H 1 resistance gene in potato have been produced by Janssen et al [57] and with the help of these pure lines, they provided the only clear example of Mendelian proof for a gene-for-gene relation between a plant and a nematode [3,56]. Breeding attention has focussed on dominant resistance genes for economically important crops and a select number of them are currently the subject of RFLP-mapping programs as a prelude to the isolation of the actual resistance genes [4,32,46,63,65,76,86]. A potentially faster source of resistance genes may come from the Arabidopsis genome although an extensive screen with 74 ecotypes yielded no resistance against H. schachtii [ 102].…”
Section: Resistance Reactions Against Nematodesmentioning
confidence: 99%
“…To translate the genetic distances of the markers into physical distances we have constructed physical maps of the two closest markers bracketing Mi, GP79 and Aps-1, using a set of rarely cutting restriction enzymes and pulsed-field gel electrophoresis (PFGE). It is shown that these two [21]). markers and two other markers (H3F8 and H4H 10) which map genetically to the same locus as Aps-1 [21, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a variety of tightly linked molecular markers have been identified including the acid phosphatase-1 (Aps-1)gene [1,12,33,39] and various RFLP [21,23] and RAPD [24] markers. These markers have been ordered into a highresolution molecular linkage map of the Mi region [21,28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations